ОСОБЛИВОСТІ ЗАСТОСУВАННЯ МИТНО-ТАРИФНИХ ПІЛЬГ В УКРАЇН - Злепко, Надія Петрівна (Науковий журнал «Світ фінансів», 2017)
Злепко Н. П. Особливості застосування митно-тарифних пільг в Україні. Розглянуто особливості застосуваннямитнотарифних пільг в Україні та їх вплив на формування дохідної частини державного бюджету. Окреслено функціональні напрямки дії окремих видів митнотарифних пільг та здійснено комплексну оцінку їх застосування в Україні. Обґрунтовано доцільність зменшення кількості митнотарифних пільг в Україні. Zlepko N. The Ef fectiveness of Custom and Tariff Privileges Implementation in Ukraine. The article deals with special features of the using of customs privileges in Ukraine. On the basis of the statistical data analysis for the number of the past years the influence of these privileges for the state budget revenue is investigated. The author fixes the main functions of some forms of customs privileges and realizes the complex opinion of their using in Ukraine. The sense of diminution of the number of customs privileges in Ukraine is substantiated.